Burst Assembly Framework for High Speed Optical Network - Saini, H; K. Garg, A (International Journal of Engineering and Technology, 2018)
Optical Burst Switching (OBS) is promising technique to support requirements of high speed optical networks. OBS network ingress node assembles packets into bursts. Burst assembly criteria have to be optimally chosen based on network requirements. In this paper, burst assembly framework is presented which can support optimal time/size value selection during burst formation. It is observed that, network with high timeout supports high Transmission Control Protocol (TCP) throughput for a range of burst size. For lower burst timeout values, throughput performance degrades only for small size bursts and further reduction in timeout threshold degrades throughput for range of burst size.Â Â